A brief history of education in Peru - Apaza Romero, Abel (2016)
This paper is a theoretical review and seeks to identify the key factors in the success achieved in the quality of education in developed countries, and also discloses the history of Adventist education in Peru and its fundamental aspects. This study was conducted based on works by historians, analysts educational articles and texts of the Spirit of Prophecy. It is concluded that the key factors for achieving economic and social success of a nation lies in the connection between action and knowledge, between research and the training of professionals serving the needs of the state, an education based on service neighbor